Agave albopilosa (Agavaceae, subgénero Littaea, grupo Striatae), una especie nueva de la Sierra Madre Oriental en el noreste de México - Cabral Cordero, Ismael; Villarreal Quintanilla, José Ángel; Estrada Castillón, Eduardo A. (Instituto de Ecología, A.C., 2007)
Agave albopilosa is described as a new species. It is a small plant, among the agaves of the Striatae group, growing in the Sierra Madre Oriental. Its most notorious feature is a ring of hairs near the end of the leaves, just below the terminal thorn. The flowers are characteristic of the group, more similar to the ones in A. stricta, slightly campanulate but with shorter lobes, and also a shorter fruit. An illustration and a key to separate the species of the group are provided.